Evaluation of the ability of chlorine to inactivate selected organisms from the biofilm of a drinking water distribution system simulator following a long-term wastewater cross-connection. Issue 2 (1st March 2004) - Gibbs, Shawn G; Meckes, Mark C; Green, Christopher F; Scarpino, Pasquale V
Abstract : The drinking water distribution system simulator (DSS) from the U.S. EPA was operated with a direct cross-connection of 0.3% wastewater to system volume per day for 70 d. During the cross-connection, tap water, wastewater, and system discharge water were monitored to ensure that the wastewater cross-connection was the source of study organisms and that these organisms were present in the water column of the DSS. The effectiveness of free chlorine levels of 0, 1, 2, and 5 mg/L to inactivate microbes in biofilms on PVC and ductile iron coupons following a wastewater cross-connection was determined. A reduction in organisms occurred after 12 h for both non-chlorinated PVC and ductile iron coupons. This suggests that the study organisms were able to adhere to the biofilm, but were not able to remain in the biofilm. The study organisms were inactivated both in the biofilm and in the water column. Water column data showed that biofilm released culturable heterotrophs and endospores into the water column throughout the 72 h evaluation period at all chlorine levels evaluated. Key words : biofilm, chlorine, wastewater, drinking water, microorganisms, cross-connection.